Implementasi Pemenuhan Hak Restitusi Bagi Anak Korban Kekerasan Seksual Pada Tahap Penuntutan (Studi di Kejaksaan Negeri Kabupaten Malang) - Kristo Saputra; Yana Indawati (Sekolah Tinggi Ilmu Hukum Sumpah Pemuda, 2026)
This study examines the implementation of restitution rights for child victims of sexual violence during the prosecution phase at the Malang Regency District Attorney’s Office. Pursuant to Article 71D (1) of Law No. 35 of 2014 on Child Protection and Government Regulation No. 43 of 2017, every child victim is entitled to restitution through the courts. Using an empirical legal research method, the results indicate that the implementation of restitution has generally adhered to applicable regulations; however, inconsistencies persist in practice, such as the absence of clear time limits and insufficient information provided to victims from the prosecution stage onward. Other barriers include minimal prosecutor involvement from the outset, low victim awareness, and weak inter-agency coordination. This study recommends enhancing prosecutors’ capacity through continuous training, expanding public awareness campaigns, and strengthening coordination among prosecutors, investigators, and the Witness and Victim Protection Agency.